Friendship and the Grounds of Reasons - Jeske, Diane (Les ateliers de l'éthique / The Ethics Forum, 2008)
Friendship and other intimate relationships have created difficulties for moral philosophers. While morality seems to require us to remain impartial between persons, friendship seems to generate demands or obligations of partiality toward our intimates. But the difficulty can be removed once we cease to focus on categorizing reasons as moral or non-moral. This tendency to divide reasons into categories of moral vs. non-moral leads us to give those that we label ‘moral’ pride of place and to assume that the category must be uniform. If we abandon these assumptions, then reasons of intimacy or friendship will no longer be so puzzling. We will then be able to see that all reasons, in the end, are importantly egocentric, and that deliberation must always proceed from an egocentric perspective.